Cuscuta epithymum Murr. crude extract pre-conditioning protects C6 cells from L-glutamate-induced neurotoxicity - Masoumeh Pourhadi; Zahra Niknam; Rasoul Ghasemi; Mina Soufi Zomorrod; Vahid Niazi; Mehrdad Faizi; Hakimeh Zali; Faraz Mojab (BMC, 2022)
Abstract Background Cuscuta epithymum Murr. (C. epithymum), as an herbal medicine, has played an anti-cancerous role in various studies; however, its possible neuroprotective effects have been neglected. Here, we aimed to investigate the protective effects of C. epithymum seeds crude extract and different fractions on rat glioblastoma cells (C6) in L-glutamate oxidative condition. Methods Initially, the total phenolic content of C. epithymum crude extract and the fractions (all produced by maceration method) was determined. Subsequently, C6 cells were pre-treated with the various concentrations of crude extract and fractions 24 h before L-glutamate exposure. Likewise, C6 cells were treated with the same concentrations of crude extract and fractions 24 h after exposure to L-glutamate. The cell viability and morphology were compared in crude extract and fractions groups, then superoxide dismutase (SODs) activity, reactive oxygen species (ROS), and malondialdehyde (MDA) levels were measured. The flow cytometry test was used to study C. epithymum crude extract's effects on the cell cycle and also to quantify the apoptosis, necrosis, and live cells population in different groups. Results C. epithymum crude extract and fractions (hexanoic, dichloromethanolic, and methanolic) had concentration-dependent cytotoxicity (IC50:126.47, 2101.96, 140.97, and 218.96 µg/ml, respectively). The crude extract and methanolic fraction contained phenolic compounds (55.99 ± 2.795 and 50.80 ± 2.969 mg gallic acid/g extract), while in hexanoic and dichloromethanolic fractions, the phenolic content was undetectable. In the cell viability assay, in comparison to fractions, the crude extract showed a more protective effect against glutamate-induced oxidative condition (P < 0.0001). The crude extract increased the SODs activity (P < 0.001) and decreased MDA and ROS levels (P < 0.0001) in comparison to the glutamate group. The crude extract significantly increased the population of cells in G1 (from 63.04 to 76.29) and decreased the percentage of cells in G2 (from 11.56 to 6.7) and S phase (from 25.4 to 17.01). In addition, it decreased the apoptotic and necrotic cell populations (from 34 to 17.1) and also increased the percentage of live cells (from 66.8 to 83.4 percent) in the flow cytometry test. Conclusion C. epithymum crude extract plays a neuroprotective role by activating the defense mechanisms in cell against the oxidative condition.